ATM in immunobiology: From lymphocyte development to cancer immunotherapy - Ji-Hoon Lee (Translational Oncology)
Ataxia Telangiectasia Mutated (ATM) is a protein kinase traditionally known for its role in DNA damage response and cell cycle regulation. However, emerging research has revealed its multifaceted and crucial functions in the immune system. This comprehensive review explores the diverse roles of ATM in immune regulation, from lymphocyte development to its involvement in cancer immunotherapy. The review describes ATM's critical functions in V(D)J recombination and class switch recombination, highlighting its importance in adaptive immunity. It examines ATM's role in innate immunity, particularly in NF-κB signaling and cytokine production. Furthermore, the review analyzes the impact of ATM deficiency on oxidative stress and mitochondrial function in immune cells, providing insights into the immunological defects observed in Ataxia Telangiectasia (A-T). The article explores ATM's significance in maintaining hematopoietic stem cell function and its implications for bone marrow transplantation and gene therapy. Additionally, it addresses ATM's involvement in inflammation and immune senescence, linking DNA damage response to age-related immune decline. Finally, this review highlights the emerging role of ATM in cancer immunotherapy, where its inhibition shows promise in enhancing immune checkpoint blockade therapy. This review synthesizes current knowledge on ATM's functions in the immune system, offering insights into the pathophysiology of ATM-related disorders and potential therapeutic strategies for immune-related conditions and cancer immunotherapy.